The Moon Hoax? Conspiracy Theories on Trial - Eversberg, Thomas (Science and Fiction, 2019)
This book is about the American moon-landings - and about the doubts expressed ever since concerning the reality of these landings. Were the moon landings really just a huge and cleverly executed hoax? Eversberg explains the best-known claims and conspiracy theories and analyses the evidence with the help of detailed full-colour images, as well as numerous film documents that can be accessed directly from the book. He addresses both the persistent older claims and more recently devised doubts. The book will inform and entertain a wide range of readers interested in space exploration and tells a gripping story covering physics, politics and history.